Experimental Research on Compact Pump-free LiBr Absorption Refrigeration System - 谷雅秀; 吴裕远; 张林颖; 柯欣; 王艺 (Zhileng xuebao)
A compact solar pump-free LiBr absorption refrigeration system was set up with new-style devices such as falling film absorber,falling film evaporator,lunate thermosiphon elevation tube. In order to improve the performance of the whole system,a second generator was designed to maintain the higher differential concentration and absorptivity in lower initial solution concentration (46%-54%) and to enhance the performance of absorber. The yield of distilled water increases by 1.68 times as compared with that of the system without a second generator . The second generator also helps increase the pressure difference between the evaporator and the condenser to improve the performance of the whole cycle. The average coefficient of performance (COP) reaches up to 0.725.